1993
DOI: 10.1042/bj2950427
|View full text |Cite
|
Sign up to set email alerts
|

The cytoplasmic domain of C-CAM is required for C-CAM-mediated adhesion function: studies of a C-CAM transcript containing an unspliced intron

Abstract: Cell-CAM105 (also named C-CAM) is a cell surface glycoprotein involved in intercellular adhesion of rat hepatocytes. It has four extracellular immunoglobulin (Ig) domains, a transmembrane domain and a cytoplasmic domain and therefore is a member of the Ig supergene family. We have characterized multiple cDNAs of the C-CAM genes in rat intestine. Sequence analyses showed that rat intestine contained not only the previously reported L-form and S-form C-CAMs (renamed C-CAM1 and C-CAM2 respectively) but also a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2

Year Published

1995
1995
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 37 publications
2
52
2
Order By: Relevance
“…Previous studies in myoblast culture systems (Rojas et al, 1996) and studies of C-CAM expression during liver development (Cheung et al, 1993b;Mowery and Hixson, 1991;Thompson et al, 1993) have shown that C-CAM (or BGP) accelerates di erentiation of myoblasts in vitro and is associated with the functional di erentiation of hepatocytes in the developing liver, respectively. However, C-CAM1 expression appeared to induce a less organized or di erentiated state in the PC-3 nude mouse tumors, evidenced by the decrease in number or absence or glandular/ductular and cord-like structures found in control PC3-V tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in myoblast culture systems (Rojas et al, 1996) and studies of C-CAM expression during liver development (Cheung et al, 1993b;Mowery and Hixson, 1991;Thompson et al, 1993) have shown that C-CAM (or BGP) accelerates di erentiation of myoblasts in vitro and is associated with the functional di erentiation of hepatocytes in the developing liver, respectively. However, C-CAM1 expression appeared to induce a less organized or di erentiated state in the PC-3 nude mouse tumors, evidenced by the decrease in number or absence or glandular/ductular and cord-like structures found in control PC3-V tumors.…”
Section: Discussionmentioning
confidence: 99%
“…C-CAM1, the rat homolog of human biliary glycoprotein I (BGPI), is a member of the carcinoembryonic antigen (CEA) family of Ig-like cell adhesion molecules (Cheung et al, 1993b;Culic et al, 1992). In rat liver, C-CAM1, also known as L-form, is the longer of the two major splice variants that vary in the length of their cytoplasmic domains (71 versus 10 amino acids).…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasmic domain of C-CAM1 contains 71 amino acids that are encoded by four exons, i.e., exons 6 ± 9 (Cheung et al, 1993a;Najjar et al, 1993). The membrane-proximal 6 amino acids together with the transmembrane domain is encoded by exon 6, while the rest of the cytoplasmic sequence was encoded by exons 7, 8 and 9 (each with 18, 10 and 35 amino acids, respectively).…”
Section: Adhesion Activity and Icap-80 Associationmentioning
confidence: 99%
“…While messages for both L-form and S-form C-CAM were detected in the DLP and the presence of C- (Cheung et al, 1993a) and the region used in the preparation of the antisense RNA probe. The restriction map and exon arrangement of the C-CAM1 genomic clone are shown.…”
Section: Localization Of C-cam Isoforms In Dlpmentioning
confidence: 98%
“…L-and Sform C-CAM, the predominant isoforms in the rat, are generated from a single gene by alternative splicing (Cheung et al, 1993a;Najjar et al, 1993). L-form C-CAM has a 71-amino acid cytoplasmic domain.…”
Section: Introductionmentioning
confidence: 99%